A new method for simultaneous optimum design of structural and control systems. (November 2015) - Jung, Ui-Jin; Park, Gyung-Jin
Highlights: A new method is proposed for the simultaneous optimum design of structural and control systems. Equivalent static loads are utilized for the optimization process. The proposed method optimizes the control forces as well as the structural variables. The proposed method can efficiently solve large scale dynamic response optimization problems. Abstract: An optimization method is proposed for the simultaneous design of structural and control systems using the equivalent static loads. The two structural and control systems are not completely independent and hence must be considered in a unified fashion. Furthermore, the integrated system should be designed to exhibit a good performance in the time domain. The analysis of the integrated system should be conducted for the transient-state in a dynamic manner. The constraints for structural and control systems are defined in the time domain as well. Therefore, a small scale structural analysis problem may easily become a large scale optimization problem. A new equivalent static loads (ESLs) method, which deals with the structural design variables as well as the control design variables, is proposed to solve large scale problems. A finite element dynamic equation is defined with control forces and a dynamic response optimization problem is formulated. Linear static response optimization is carried out with the ESLs. The control forces for the linear static response optimization are considered as design variables. Shape variables are utilized to handle the design variables for the control forces. Several test problems are solved to validate the proposed method.